Violent Conflict Exposure in Nigeria and Economic Welfare - John Chiwuzulum Odozi; Ruth Uwaifo Oyelere (Institute of Labor Economics (IZA), 2019)
Several papers have attempted to estimate and document the impact of conflict on several education, health and socioeconomic outcomes. One lesson from the past research is the heterogeneity in the effect of violent conflict across and within countries. In this paper we attempt to estimate the casual impact of conflict in Nigeria on welfare related outcomes. The 2009 insurgence of Boko Haram and the Fulani herdsmen versus farmers conflicts have led to a significant increase in violent conflict in the North Eastern and Central parts of Nigeria. However, bouts of violent conflict have existed in different communities across the country since independence. We estimate the average effect of violent conflict exposure on welfare, across Nigeria using the three waves of the Nigerian General Household Survey (GHS) panel combined with The Armed Conflict Location & Event Data (ACLED). Employing a fixed effect approach, our results suggest that recent and long term exposure to conflict increased the incidence, intensity and severity of poverty in Nigeria. In addition we find that exposure to violent conflict also decreased household income.
Keywords: I10; I30; O1; D74; 330; violence; Nigeria; conflict; Boko Haram; economic welfare; poverty